EFEKTIVITAS PRODUCT PLACEMENT HYUNDAI PADA DRAMA KOREA DESCENDANTS OF THE SUN TERHADAP BRAND AWARENESS SURVEY PADA PENONTON DRAMA KOREA DOTS DI TANGERANG - Krisna Ayu Wulandari (Jurnal Visi Komunikasi, 2020)
The company started to use an advertising technique that was deemed sufficient, namely by using product placement or brand placement. This study was to determine the effectiveness of product placement on the brand awareness survey of the Korean Drama Descendant of The Sun audience in Tangerang. The paradigm used in this research is positivistic, with a quantitative approach to survey methods for Korean drama audiences Descendant of the Sun with non-probability sampling using accidental sampling. The results showed that the product placement made by Hyundai in the Korean drama Descendant of the Sun contributed 44.7% to the brand awareness of the Korean drama Descendant of the sun audience